2017
DOI: 10.1155/2017/3802381
|View full text |Cite
|
Sign up to set email alerts
|

Predictions for the Isolated Prompt Photon Production at the LHC ats= 13 TeV

Abstract: The prompt photon production in hadronic collisions has a long history of providing information on the substructure of hadrons and testing the perturbative techniques of QCD. Some valuable information about the parton densities in the nucleon and nuclei, especially of the gluon, can also be achieved by analysing the measurements of the prompt photon production cross section whether inclusively or in association with heavy quarks or jets. In this work, we present predictions for the inclusive isolated prompt ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 107 publications
(153 reference statements)
0
7
0
Order By: Relevance
“…However, the application of the isolation criteria in the measurements reduces the parton-to-photon fragmentation contribution to the total cross section. Indeed, the most recent measurements of ATLAS experiment [38,39], performed with the isolation requirement P T iso < 4.8 GeV + 4.2 10 −3 P T γ calculated within a cone of size ΔR = 0.4, reduce significantly the fragmentation components, as indicated in [40]. Furthermore, the contributions from the fragmentation decrease considerably when |cos θ * | → 0 [41,42].…”
Section: Direct Photon Productionmentioning
confidence: 97%
“…However, the application of the isolation criteria in the measurements reduces the parton-to-photon fragmentation contribution to the total cross section. Indeed, the most recent measurements of ATLAS experiment [38,39], performed with the isolation requirement P T iso < 4.8 GeV + 4.2 10 −3 P T γ calculated within a cone of size ΔR = 0.4, reduce significantly the fragmentation components, as indicated in [40]. Furthermore, the contributions from the fragmentation decrease considerably when |cos θ * | → 0 [41,42].…”
Section: Direct Photon Productionmentioning
confidence: 97%
“…However, looking for similar quantities with more benefits is really of interest. It has been indicated that the ratio of distributions for different rapidity regions can be a good option [87]. In Refs.…”
Section: B Rapidity Normalized Distributionsmentioning
confidence: 99%
“…Since the PDFs are the nonperturbative objects, they have to be constrained in a global analysis to experimental data [3,4,5,6,7,8,9,10,11,12,13]. In this vein, the determination of the gluon distribution both in the nucleon [93] and nuclei [94], and also the sea quark distributions and possible asymmetries between them is of particular importance. Nowadays, thanks to many experiments provide a wide range of accurate data including the DIS, pp and pp collider measurements, our knowledge of the valence quarks, and to a large extent, sea quarks and gluon distributions is satisfying.…”
Section: The S − S Asymmetry In the Protonmentioning
confidence: 99%